2020
DOI: 10.1108/f-04-2020-0038
|View full text |Cite
|
Sign up to set email alerts
|

Productivity as a value parameter for FM and CREM

Abstract: Purpose This paper aims to investigate how facilities management (FM) and corporate real estate management (CREM) can add value to organisations by contributing to improved productivity of knowledge workers, and to explore interrelationships between productivity, employee satisfaction and other value parameters. Design/methodology/approach This is a literature research of possible contributions of FM and CREM to improved labour productivity in relation to five activity areas of FM/CREM (portfolio management,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Besides, people have become more aware of the impact of health and well-being on our quality of life and the risk of health complaints, illness orin worst casesburnout (Appel-Meulenbroek et al, 2020). The relationship between physical workplace characteristics and health and wellbeing has been explored by a variety of studies, using reviews of the literature (Forooraghi et al, 2020;Van der Voordt, 2021), surveys (Cordero et al, 2020), case studies (Bauer, 2020) and conducting short-term experiments using mobile devices (Nelson and Holzer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, people have become more aware of the impact of health and well-being on our quality of life and the risk of health complaints, illness orin worst casesburnout (Appel-Meulenbroek et al, 2020). The relationship between physical workplace characteristics and health and wellbeing has been explored by a variety of studies, using reviews of the literature (Forooraghi et al, 2020;Van der Voordt, 2021), surveys (Cordero et al, 2020), case studies (Bauer, 2020) and conducting short-term experiments using mobile devices (Nelson and Holzer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The same classification is used in a journal paper concerning productivity as a value parameter by Jensen and van der Voordt (2020). They write that the boundaries between these scopes are not always sharp.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of the authors’ knowledge, this study presents the first attempt to test and develop added value indicators within the context of a developing country by taking a systematic content validation procedure. Notwithstanding the rigours processes of the content validation, it is worth noting that added value of real estate is a multi-dimensional concept which is linked to stakeholder’s perspective and to some extent sector dependent (Jensen and van der Voordt, 2020a, 2020b; van der Zwart and van der Voordt, 2013). The study thus recommend that future studies should determine sector specific added value parameters tailored to the needs of specific organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research by Yang et al (2019) identified knowledge-based economy, digitized nomad, mobile technologies that is influencing new lifestyles driven by creativity and innovation as essential indicators for co-working spaces while and Jensen and van der Voordt (2020b) set the argument on the relevance of real estate value-adding and workplaces, employees and society as well as its impact on client satisfaction, productivity and organizational cost. In this regard, the authors establish that portfolio and project management, property and service management can contribute in diverse ways to add value to workplace and productivity of organization.…”
Section: Review Of Literature On Corporate Real Estate Added Valuementioning
confidence: 99%